SMARTPHONE USE IN EMPLOYEE PERFORMANCE IMPROVEMENT - Rachmad Bambang; A. Reski Fauziah Putri (Journal of Entrepreneur, Business and Management, 2023)
The main purpose of this study is to determine the influence of smartphones in supporting employee performance in the guest house and education room at the office of the education quality assurance agency (LPMP) South Sulawesi. This research uses a quantitative descriptive approach, namely conducting research by bringing clear problems that are formulated and answered by hypotheses. Based on the results of previous research and discussion, the author concludes that the use of smartphones has a positive and significant effect on employee performance in the guest house and education room at the office of the South Sulawesi Education Quality Assurance Agency (LPMP).